Titanium-tantalum synergetic co-doped solid oxide battery air electrode material and preparation method thereof
The BaCo0.4Fe0.4Ti0.1Ta0.1O3-δ (BCFTT) air electrode material prepared by solid phase method reduces the amount of cobalt by co-doping of titanium and tantalum, solving the problems of high cost and poor stability of traditional solid oxide batteries, and achieving efficient operation under medium and low temperature conditions.
Patent Information
- Application Number
- CN202411347721.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional solid oxide batteries have high cost and poor cycle stability due to high operating temperatures, and limited cobalt resources and high thermal expansion coefficient are not conducive to medium and low temperature operations, which limits their application.
The BaCo0.4Fe0.4Ti0.1Ta0.1O3-δ (BCFTT) air electrode material was prepared by solid phase method, and the amount of cobalt was reduced by co-doping of titanium and tantalum, thereby improving the conductivity, ORR activity and cyclic stability of the material.
A solid oxide battery operating under medium and low temperature conditions is realized, with more stable phase structure and thermal stability, and improved battery output performance and cycle stability.
Smart Images

Figure CN119674108A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a perovskite-type solid oxide battery air electrode material composition and a preparation method thereof, and more specifically to a solid oxide battery air electrode material BaCo prepared by a solid phase method. 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ (BCFTT) and its preparation method and application belong to the technical field of solid oxide batteries. Background Art
[0002] At present, the world is in urgent need of clean energy, and solid oxide cells (SOCs) are considered to be one of the high-efficiency energy conversion devices that can solve energy crises and environmental problems. Compared with traditional thermal power generation technology, SOCs have the advantages of low emissions, wide fuel applicability and all-solid-state configuration, and have good application prospects at present.
[0003] However, traditional solid oxide batteries have high costs and poor cycle stability due to their high operating temperatures, which seriously hinders their large-scale commercialization. Therefore, in order to reduce material costs and improve the stability of solid oxide batteries, lowering the operating temperature is a research hotspot. However, as the operating temperature decreases, the performance of traditional solid oxide batteries is limited. The development of battery air electrode materials with high oxygen reduction reaction (ORR) activity at low temperatures is a breakthrough direction in battery research.
[0004] Traditional cobalt-based perovskite oxide materials have been widely studied in medium and low temperature solid oxide batteries, but the limited resource reserves of cobalt and the high thermal expansion coefficient of cobalt are not conducive to the operation of solid oxide batteries at medium and low temperatures, which limits their application in solid oxide batteries. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a solid oxide battery air electrode material that reduces the amount of cobalt used and needs to maintain good battery performance. In the present invention, other metal elements are used to reduce their use, specifically titanium, tantalum and other elements. The solid oxide battery air electrode material provided in the present invention and its preparation method and application improve the performance of the air electrode. The air electrode has a more stable phase structure and thermal stability, and at the same time has higher conductivity, stronger ORR activity and cycle stability, so that the solid oxide battery can operate under medium and low temperature conditions.
[0006] A solid oxide battery air electrode material, whose general chemical formula is ABO 3-δ , molecular formula: BaCo x Fe y Ti m Tan O 3-δ , where δ represents the oxygen vacancy content.
[0007] x or y ∈ [0.3, 0.5], m or n ∈ [0.05, 0.15].
[0008] In one embodiment, 0≤δ≤1.
[0009] In one embodiment, the molecular formula is: BaCo 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ .
[0010] The method for preparing air electrode material of solid oxide battery comprises the following steps: preparing by solid phase method according to stoichiometric ratio.
[0011] The steps of the solid phase method include:
[0012] Step 1: weigh a certain mass of Ba, Co, Fe, Ti and Ta oxides according to the stoichiometric ratio, add an appropriate amount of dispersant, and mix the solution to obtain a uniform slurry by ball milling; and obtain a precursor after drying;
[0013] In the second step, the precursor obtained in the first step is placed in a muffle furnace and calcined in an air atmosphere to obtain the desired air electrode material.
[0014] In one embodiment, the drying condition of the precursor is baking under a sodium lamp at 140-180° C. for 2-3 hours.
[0015] In one embodiment, the calcination condition is calcination at 1000° C. for 5-10 h in an air atmosphere, with a heating rate of 2-5° C. / min.
[0016] In one embodiment, the dispersant is ethanol.
[0017] In one embodiment, the ball milling process is performed by a high energy ball mill at a rotation speed of 200-600 rpm for 1-10 hours.
[0018] The above-mentioned solid oxide battery air electrode material is used in the battery air electrode.
[0019] Beneficial Effects
[0020] The solid oxide battery air electrode material involved in the present invention has the following effects:
[0021] (1) This invention synthesizes BaCo by a solid phase method 0.4 Fe 0.4 Ti 0.1 Ta0.1 O 3-δ (BCFTT) air cathode material, the various elements in the material are evenly distributed, and the synthesis method is simple and efficient.
[0022] (2) BaCo, a solid oxide battery air electrode material prepared by solid phase method 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ (BCFTT). With high battery output performance, the single cell with BCFTT as the air electrode showed very excellent performance, with peak power densities of 1.7 W cm at 650°C, 600°C, 550°C and 500°C respectively. -2 、1.4W cm -2 , 1.1W cm -2 and 0.79 W cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 These are the XRD spectra of BSCF, BCFZY, BCFTN, and BCFTT after calcining at 1000°C in air atmosphere for 5 h and then naturally cooling to room temperature;
[0024] Figure 2 The BCFTT+SDC electrode material was calcined at 1000℃ in air atmosphere for 240h, and the XRD spectrum of BCFTT+SDC was tested after the material was naturally cooled to room temperature.
[0025] Figure 3 The STEM-EDS spectrum of BCFTT air electrode material is shown;
[0026] Figure 4 It is the oxygen non-stoichiometric ratio of the four air electrode materials BSCF, BCFZY, BCFTN and BCFTT in the temperature range of 500-650℃;
[0027] Figure 5 It is the ECR response curve spectrum of four air electrode materials: BSCF, BCFZY, BCFTN and BCFTT in the temperature range of 500-700℃;
[0028] Figure 6 It is the fitting of four materials: BSCF, BCFZY, BCFTN and BCFTT. chem , k chem A map of values;
[0029] Figure 7It is the Arrhenius curve of four air electrodes: BSCF, BCFZY, BCFTN, and BCFTT in the temperature range of 500-700℃
[0030] Figure 8 This is the Nyquist plot of the BCFTT air electrode of a symmetric battery based on SDC electrolyte and BCFTT as electrode tested at 500°C and 600°C;
[0031] Fig. 9 This is the stability test graph of the impedance of a symmetrical battery based on SDC electrolyte and BCFTT as electrode at 500°C; Fig.10 A single cell with the structure of BCFTT|SDC|Ni-SDC fuel electrode supported type was prepared with Ni-SDC as the fuel electrode, SDC as the electrolyte and BCFTT as the air electrode. The IP and IV performance curves were obtained under the condition of air as the fuel. Fig.11 The XRD spectra of BCTN and BCTT oxides prepared in Example 1 are shown after calcining at 1000°C in air atmosphere for 5 hours and then naturally cooling to room temperature. Fig.12 Nyquist plot of the BCFTT air electrode of a symmetric battery based on SDC electrolyte with BCTT and BCTN as electrodes tested at 650-500°C. Fig.13 These are the thermal expansion test result diagrams of SCTT, BCTT, BCFTT, SCTN, BCTN, and BCFTN. DETAILED DESCRIPTION
[0032] The present invention relates to an iron-titanium-tantalum synergistically co-doped barium-cobalt-based perovskite solid oxide battery air electrode material and a preparation method thereof. 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ Since Ba can increase the oxygen vacancy concentration of the air cathode material, and partial Fe substitution for Co can stabilize the perovskite structure and reduce the thermal expansion coefficient of the material, in order to further confirm the synergistic effect of co-doping, we synthesized Ti / Ta co-doped BaCo by high temperature solid phase method. 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ The influence of B-site co-doping on the phase structure and electrochemical performance of air cathode materials is studied to obtain materials with high activity and stability. The above materials can be prepared by solid phase method according to the composition ratio.
[0033] Example 1
[0034] BaCo, air electrode material for medium and low temperature solid oxide batteries 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ (BCFTT) was prepared by solid phase method, and the specific steps are as follows:
[0035] (1) According to BaCo 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ 9.8670g of BaCO3, 1.6053g of Co3O4, 1.5969g of Fe2O3, 0.39935g of TiO2 and 1.1047g of Ta2O5 were weighed in a clean ball mill jar according to the stoichiometric ratio of (BCFTT), and an appropriate amount of ethanol was added as a dispersant. 45ml of ethanol was weighed according to the molar ratio of ethanol: total metal ions of 1-2:1, and the mixed slurry was ball milled in a high-energy ball mill at a speed of 400rpm for 1-2h.
[0036] (2) The ball-milled precursor is then baked at 140-180°C under a sodium lamp for 2-3 hours.
[0037] (3) The dried precursor is placed in a high-temperature muffle furnace and calcined at 1100°C for 5 hours to obtain the required BCFTT air electrode powder.
[0038] Example 2
[0039] BaCo, air electrode material for medium and low temperature solid oxide batteries 0.4 Fe 0.4 Ti 0.1 Nb 0.1 O 3-δ (BCFTN) was prepared by solid phase method, and the specific steps are as follows:
[0040] (1) According to BaCo 0.4 Fe 0.4 Ti 0.1 Nb 0.1 O 3-δ9.8670g of BaCO3, 1.6053g of Co3O4, 1.5969g of Fe2O3, 0.39935g of TiO2 and 0.6645g of Nb2O5 were weighed in a clean ball mill jar according to the stoichiometric ratio of (BCFTN), and an appropriate amount of ethanol was added as a dispersant. 45ml of ethanol was weighed according to the molar ratio of ethanol: total metal ions of 1-2:1, and the mixed slurry was ball milled in a high-energy ball mill at a speed of 400rpm for 1-2h.
[0041] (2) The ball-milled precursor is then baked at 140-180°C under a sodium lamp for 2-3 hours.
[0042] (3) The dried precursor is placed in a high-temperature muffle furnace and calcined at 1100°C for 5 hours to obtain the required BCFTN air electrode powder.
[0043] Comparative Example 1
[0044] BaCo, air electrode material for medium and low temperature solid oxide batteries 0.8 Ti 0.1 Ta 0.1 O 3-δ The specific steps for the preparation of (BCTT) are as follows
[0045] (1) According to BaCo 0.8 Ti 0.1 Ta 0.1 O 3-δ 9.8670 g of BaCO3, 3.2107 g of Co3O4, 0.3994 g of TiO2 and 1.1047 g of Ta2O5 were weighed in a clean ball mill jar according to the stoichiometric ratio of (BCTT), and an appropriate amount of ethanol was added as a dispersant. 45 ml of ethanol was weighed according to the molar ratio of ethanol: total metal ions of 1-2:1, and the mixed slurry was ball milled in a high-energy ball mill at a speed of 400 rpm for 1-2 hours.
[0046] (2) The ball-milled precursor is then baked at 140-180°C under a sodium lamp for 2-3 hours.
[0047] (3) The dried precursor is placed in a high-temperature muffle furnace and calcined at 1100°C for 5 hours to obtain the desired BCTT air electrode powder.
[0048] BaCo, air electrode material for medium and low temperature solid oxide batteries 0.8 Ti 0.1 Nb 0.1 O 3-δ The specific steps for preparing (BCTN) are as follows:
[0049] (1) Taking BCTN as an example, according to BaCo 0.8 Ti0.1 Nb 0.1 O 3-δ 9.8670 g of BaCO3, 3.2107 g of Co3O4, 0.3994 g of TiO2 and 0.6645 g of Nb2O5 were weighed in a clean ball mill jar according to the stoichiometric ratio of (BCTN), and an appropriate amount of ethanol was added as a dispersant. 45 ml of ethanol was weighed according to the molar ratio of ethanol: total metal ions of 1-2:1, and the mixed slurry was ball milled in a high-energy ball mill at a speed of 400 rpm for 1-2 hours.
[0050] (2) The ball-milled precursor is then baked at 140-180°C under a sodium lamp for 2-3 hours.
[0051] (3) The dried precursor is placed in a high-temperature muffle furnace and calcined at 1100°C for 5 hours to obtain the desired BCTN air electrode powder.
[0052] Comparative Example 2
[0053] BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3-δ (BCFZY), Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) is prepared by sol-gel method. The specific preparation steps are as follows:
[0054] (1) Taking BCFZY as an example, according to BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3-δ 13.0670 g of Ba(NO3)2, 5.2206 g of Co(NO3)2·6H2O, 8.0800 g of Fe(NO3)3·9H2O, 2.1466 g of Zr(NO3)2·5H2O, and 1.9150 g of Y(NO3)3·6H2O were weighed in a clean beaker according to the stoichiometric ratio. An appropriate amount of deionized water was added and stirred to dissolve on an electric stirring table to obtain a clear solution. 29.224 g of ethylenediaminetetraacetic acid and 42.028 g of hydrated citric acid were weighed as complexing agents and dissolved in deionized water according to the molar ratio of ethylenediaminetetraacetic acid: monohydrated citric acid: total metal ions of 1:2:1.
[0055] (2) After adding the solution containing the complexing agent into the solution containing the metal ions, an appropriate amount of ammonia water is added dropwise until the pH of the solution reaches between 7 and 8, and then the solution is stirred under magnetic stirring until the water is completely evaporated to obtain a gel-like substance.
[0056] (3) The gel-like substance is placed in an oven and calcined at 180°C for 5 hours to obtain the desired precursor.
[0057] (4) The precursor is placed in a high-temperature muffle furnace and calcined at 1100°C for 5 hours to obtain the required BCFZY air electrode powder.
[0058] Preparation of symmetric battery
[0059] BaCo 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ The preparation and testing method of a symmetrical battery with (BCFTT) as an electrode is as follows: (1) weigh 1 g of the air electrode powder BaCo prepared in Example 1 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ (BCFTT), 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol were poured into a high-energy ball mill. After ball milling at 400 r / min for 30 min, the desired air electrode slurry was obtained by transferring it to the culture bottle with a dropper.
[0060] (2) The prepared SDC dry-pressed battery sheet was placed on a heating table and preheated at 150°C. The prepared air electrode slurry was evenly sprayed on both sides of the electrolyte of the dry-pressed sheet using a spray gun under the push of inert gas. After the liquid evaporated completely, the sprayed dry-pressed battery was placed in a high-temperature muffle furnace and calcined at 1000°C for 2 hours to obtain the required symmetrical battery, which was used for the test of the interface impedance of the air electrode material at 500°C and 600°C and the cycle stability test.
[0061] Preparation of single cell
[0062] BaCo 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ The preparation and testing method of a single cell with (BCFTT) as the air electrode is as follows: (1) weigh 1 g of the air electrode powder BaCo prepared in Example 1. 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ (BCFTT), 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol were poured into a high-energy ball mill. After ball milling at 400 r / min for 30 min, the desired air electrode slurry was obtained by transferring it to the culture bottle with a dropper.
[0063] (2) The prepared SDC dry-pressed battery sheet was placed on a heating table and preheated at 150°C. The prepared air electrode slurry was evenly sprayed on the electrolyte surface of the dry-pressed sheet using a spray gun under the push of inert gas. After the liquid evaporated completely, the sprayed dry-pressed battery was placed in a high-temperature muffle furnace and calcined at 900°C for 2h to obtain the required single cell, which was used to test the battery performance of the air electrode material in the temperature range of 500-650°C. The peak power density of the BCFTT single cell at 650°C, 600°C, 550°C and 500°C was 1.7W cm -2 、1.4W cm -2 , 1.1W cm -2 and 0.79 W cm -2 .
[0064] 1. XRD characterization
[0065] Figure 1 The XRD spectra of the four oxides BSCF, BCFZY, BCFTN and BCFTT prepared in Example 1 after calcination at 1000°C in air atmosphere for 5 hours and then naturally cooling to room temperature are shown. The doping amounts of the B-site elements Zr, Y, Ti, Nb and Ta are all 0.1, and all the diffraction peaks on the surface match those of simple cubic perovskite (Pm-3m), and no impurity phase is generated.
[0066] Figure 2 It shows that the BCFTT+SDC electrode material was calcined in an air atmosphere at 1000℃ for 240h, and the XRD spectrum of BCFTT+SDC was tested after it was naturally cooled to room temperature. The stability of the electrode material itself and the compatibility of the electrode material and the electrolyte material usually have an adverse effect on the electrochemical stability of the electrode. It can be found that the XRD spectrum of the BCFTT+SDC powder after calcination at 1000℃ in an air atmosphere for 240h does not have any extra peaks. On the one hand, this shows that BCFTT itself has a good phase structure, and on the other hand, BCFTT and SDC electrolyte also have good compatibility.
[0067] 2. Scanning Transmission Electron Microscopy (STEM) Characterization
[0068] Figure 3 The STEM-EDS spectrum of the BCFTT air cathode material is shown. The Ba, Co, Fe, Ti and Ta elements are evenly distributed in the material without element segregation.
[0069] 3. Analysis of oxygen exchange and oxygen conduction performance
[0070] The advantage of using mixed ion conductor materials as electrodes is that they allow the oxygen reduction reaction to occur on the electrode surface, thereby obtaining higher ORR catalytic performance. In perovskite materials, oxygen vacancies are the key to the transfer of oxygen ions in the bulk phase. Perovskites with high oxygen vacancy concentrations generally have excellent oxygen ion conductivity. Studies have shown that the oxygen ion conductivity and oxygen exchange rate of air electrode materials are directly related to their oxygen non-stoichiometric ratio. A high oxygen non-stoichiometric ratio means a high oxygen vacancy concentration. High-temperature oxygen vacancies can be derived by combining the initial oxygen non-stoichiometric ratio at room temperature and thermogravimetric analysis (TGA) data.
[0071] Figure 4 The oxygen non-stoichiometric ratios of four air cathode materials, BSCF, BCFZY, BCFTN and BCFTT, are given in the temperature range of 500-650℃. The oxygen non-stoichiometric ratios of the four materials increase with increasing temperature, and the order is BCFZY>BCFTT>BCFTN>BSCF.
[0072] Figure 5 The ECR response curves of four air electrode materials, BSCF, BCFZY, BCFTN and BCFTT, in the temperature range of 500-700℃ are given.
[0073] Figure 6 Four material fitting Ds of BSCF, BCFZY, BCFTN and BCFTT are given. chem , k chem The oxygen reduction activity of the electrode material is closely related to the bulk diffusion and surface exchange capacity of the material. Therefore, the bulk diffusion coefficient (D chem ) and surface exchange coefficient (k chem ), is the ECR response curve of BSCF, BCFTN, BCFTT, and BCFZY in the temperature range of 500-700℃ and the fitted D when the oxygen partial pressure suddenly changes from 0.1atm to 0.21atm chem and k chem Curve of change with temperature. chem and k chem As the temperature increases, the D chem and k chem At the corresponding temperature, it is larger than the other three materials, and the activation energy in this temperature range is the smallest, which is 70KJ mol -1 .
[0074] 4. Symmetrical battery performance analysis
[0075] First, the electrochemical activity of BCFTT was evaluated by electrochemical impedance spectroscopy (EIS). The AC impedance spectrum of the BCFTT|SDC|BCFTT symmetric cell was tested at a temperature range of 500°C and 600°C in air. The difference between the intercepts of the high and low frequencies of the EIS on the real axis is the area specific resistance (ASR) of the electrode. The smaller the ASR value, the higher the ORR catalytic activity.
[0076] Figure 7 It is the BCFTT air electrode that has the lowest ASR activation energy among the listed air electrodes in the range of 450-600°C, and therefore has the highest ORR activity.
[0077] Figure 8 This is the Nyquist plot of the BCFTT air electrode of a symmetrical battery based on SDC electrolyte and BCFTT as electrode tested at 500℃ and 600℃. The EIS graphs at 500℃ and 600℃ respectively, in air atmosphere and under open circuit voltage test conditions. From the EIS graph, it can be seen that the impedance value of BCFTT at the two temperature points of 500℃ and 600℃ is the smallest, which is 0.0428Ωcm 2 , 0.235Ωcm 2 .
[0078] Fig. 9 This is a stability test graph of the impedance of a symmetrical battery based on SDC electrolyte and BCFTT as electrode at 500°C. In order to study its long-term chemical stability in air atmosphere, we tested it for 270 hours. Due to the long test interval, the ASR value fluctuated slightly, but overall, the impedance value of the electrode remained stable. The results show that BCFTT has stable oxygen reduction activity at medium and low temperatures.
[0079] 5. Single battery performance test
[0080] Fig.10 The single cell IP and IV curves are shown in Figure 2. A single cell with a structure of BCFTT|SDC|Ni-SDC fuel electrode support was prepared with Ni-SDC as the fuel electrode, SDC as the electrolyte, and BCFTT as the air electrode. The IP and IV curves of the single cell were obtained under the condition of air as the fuel. The single cell with BCFTT as the air electrode showed very excellent performance in the temperature range of 500-650℃. The peak power density at 650℃, 600℃, 550℃ and 500℃ was 1.7W cm -2 、1.4W cm -2 , 1.1W cm -2 and 0.79 W cm -2 .
[0081] 6. Comparative ratio related tests
[0082] Fig.11 The XRD spectra of BCTN and BCTT oxides prepared in Example 1 after calcination at 1000°C in air atmosphere for 5 hours and then naturally cooling to room temperature are shown. The results show that the diffraction peaks match the simple cubic perovskite (Pm-3m) as a whole, but are accompanied by the formation of an impurity phase (P-3m1), further indicating that partial substitution of iron is beneficial to stabilizing the phase structure stability of the air electrode material.
[0083] Fig.12 Nyquist plots of BCFTT air electrodes of symmetrical batteries based on SDC electrolyte and BCTT and BCTN as electrodes tested at 650-500°C. EIS plots of BCTT and BCTN air electrode materials under open circuit voltage test conditions in air atmosphere. At 600°C, the ASR values of symmetrical batteries based on BCTT and BCTN as electrodes are 0.35 and 0.37Ωcm, respectively. 2 .
[0084] 7. Thermal expansion test
[0085] Fig.13 The thermal expansion test results of SCTT, BCTT, BCFTT, SCTN, BCTN, and BCFTN are shown in the figure. It can be seen that Ba replacing Sr and partially replacing Co with Fe can effectively reduce the thermal expansion coefficient of the material, further improving the thermal matching between the air electrode and the electrolyte material.
Claims
1. A solid oxide battery air electrode material, characterized in that: Its general chemical formula is ABO 3-δ , molecular formula: BaCo x Fe y Ti m Ta n O 3-δ , where δ represents the oxygen vacancy content.
2. The solid oxide battery air electrode material according to claim 1, characterized in that: x or y ∈ [0.3, 0.5], m or n ∈ [0.05, 0.15].
3. The solid oxide battery air electrode material according to claim 1, characterized in that: 0≤δ≤1.
4. The solid oxide battery air electrode material according to claim 1, characterized in that: Molecular formula: BaCo 0.4 Fe 0.4 Ti 0.1 Ta 0.1 O 3-δ .
5. The method for preparing the air electrode material according to claim 1, characterized in that: The method comprises the following steps: preparing the product by a solid phase method according to a stoichiometric ratio.
6. The preparation method according to claim 5, characterized in that: In the first step, a certain mass of Ba, Co, Fe, Ti and Ta oxides are weighed according to the stoichiometric ratio, an appropriate amount of dispersant is added, and the mixed solution is ball-milled to obtain a uniform slurry; a precursor is obtained after drying; in the second step, the precursor obtained in the first step is placed in a muffle furnace and calcined in an air atmosphere to obtain the desired air electrode material.
7. The preparation method according to claim 5, characterized in that: The drying condition of the precursor is baking at 140-180°C under a sodium lamp for 2-3 hours.
8. The preparation method according to claim 5, characterized in that: The calcination conditions are calcination at 1000°C for 5-10h in an air atmosphere with a heating rate of 2-5°C / min.
9. The preparation method according to claim 5, characterized in that: The dispersant is ethanol; the ball milling process is carried out by using a high-energy ball mill at a rotation speed of 200-600 rpm for 1-10 hours.
10. Use of the solid oxide battery air electrode material according to claim 1 in battery air electrode.